Effect of Vinegar Therapy on Bacterial Growth in Diabetic Foot Ulcers - Al-Duboni, Ghada Ibraheem (Diyala Journal of Medicine, 2019)
Background: Non-healing diabetic foot ulcers is a common problem worldwide, almost 15% of all diabetic patients will develop one or more foot ulcers some of them will require amputation. Foot infections are usually caused by aerobic gram-positive bacteria in the acute cases or a mixture of aerobic gram positive, aerobic gram negative and anaerobic organisms in chronic wounds. Objectives: To assess the efficacy of vinegar therapy on bacterial growth in the process of treating diabetic foot ulcers. Materials and methods: Retrospective comparison of changes in bacterial culture, necrotic and total surface area of chronic wounds treated with either vinegar therapy or standard (control) surgical or nonsurgical therapy. Total of 30 patients with non-healing ulcers were divided into 3 groups; 10 wounds were treated with conventional therapy, 10 with vinegar therapy, and 10 with hypertonic saline. Results: Repeated measures ANOVA indicated no significant change in necrotic tissue. During the first 14 days of conventional therapy, there was no significant debridement of necrotic tissue, and heavy growth of different pathogens mainly Staphylococci, Streptococci, and Pseudomonas. During the same period with vinegar therapy, necrotic tissue decreased by an average of 4.1 cm2 (P = 0.02). After 3 weeks of therapy, conventionally treated wounds were still covered with necrotic tissue over 41% of their surface and still growth of different pathogens , whereas after only 3 weeks of therapy vinegar-treated wounds were completely debrided (P = 0.001) and 70% of cultures were negative . Vinegar therapy was also associated with hastened growth of granulation tissue and grater wound healing rates. Conclusion: Vinegar therapy was more effective and efficient in debriding non healing foot and leg ulcers in diabetic patients than was continued conventional care and associated with lower bacterial growth rates.